2005
DOI: 10.4049/jimmunol.175.9.6205
|View full text |Cite
|
Sign up to set email alerts
|

Cdc2/Cyclin B1 Interacts with and Modulates Inositol 1,4,5-Trisphosphate Receptor (Type 1) Functions

Abstract: The resistance of inositol 1,4,5-trisphosphate receptor (IP3R)-deficient cells to multiple forms of apoptosis demonstrates the importance of IP3-gated calcium (Ca2+) release to cellular apoptosis. However, the specific upstream biochemical events leading to IP3-gated Ca2+ release during apoptosis induction are not known. We have shown previously that the cyclin-dependent kinase 1/cyclin B (cdk1/CyB or cdc2/CyB) complex phosphorylates IP3R1 in vitro and in vivo at Ser421 and Thr799. In this study, we show that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…The kinase(s) responsible for IP 3 R1 phosphorylation in eggs is not yet known, although it is logical to envisage the participation of MPF and MAPK. Cdc2/cyclin B has already been shown to phosphorylate IP 3 R1 in vitro and in vivo (Li et al, 2005;Malathi et al, 2003). In addition, substratebinding motifs for this kinase were recently reported in IP 3 Rs and, consistent with this, immunoprecipitation studies in breast cancer cells have shown that cyclins and IP 3 R3 can interact (Soghoian et al, 2005).…”
supporting
confidence: 55%
“…The kinase(s) responsible for IP 3 R1 phosphorylation in eggs is not yet known, although it is logical to envisage the participation of MPF and MAPK. Cdc2/cyclin B has already been shown to phosphorylate IP 3 R1 in vitro and in vivo (Li et al, 2005;Malathi et al, 2003). In addition, substratebinding motifs for this kinase were recently reported in IP 3 Rs and, consistent with this, immunoprecipitation studies in breast cancer cells have shown that cyclins and IP 3 R3 can interact (Soghoian et al, 2005).…”
supporting
confidence: 55%
“…Mutagenesis of three residues together (Arg-391, Arg-441, and Arg-871) inhibited binding of the cdc2/CyB complex with the InsP 3 R-1 (252), suggesting they may be involved in interactions between the proteins that enable the phosphorylation of the channel. Functionally, cdc2/CyB-mediated phosphorylation enhanced the affinity of the InsP 3 -binding region for InsP 3 and enhanced InsP 3 -mediated Ca 2ϩ release from microsomes (252,288).…”
Section: Phosphorylation By Cdks/cybmentioning
confidence: 99%
“…The cyclin-dependent kinase 1/cyclin B (cdc2/CyB) complex phosphorylates InsP 3 R-1 at Ser-421 and Thr-799 and InsP 3 R-3 at Ser-795 (252,288). Mutagenesis of three residues together (Arg-391, Arg-441, and Arg-871) inhibited binding of the cdc2/CyB complex with the InsP 3 R-1 (252), suggesting they may be involved in interactions between the proteins that enable the phosphorylation of the channel.…”
Section: Phosphorylation By Cdks/cybmentioning
confidence: 99%
“…It has now been shown in somatic cells (a human T cell line) that the type I inositol trisphosphate receptor [Ins(1,4,5)P 3 R] is phosphorylated on two sites by Cdk1, leading to an increase in inositol trisphosphate [Ins (1,4,5)P 3 ] binding (Malathi et al, 2003;Li et al, 2005). This observation may partly explain the Ca 2+ rises that have been recorded during M phase in somatic cells (Ratan et al, 1986;Kao et al, 1990), during early embryogenesis (Groigno and Whitaker, 1998), and during meiotic M phase.…”
Section: Introductionmentioning
confidence: 99%